2018
DOI: 10.1016/j.jacc.2017.11.020
|View full text |Cite|
|
Sign up to set email alerts
|

Impaired Recovery of Left Ventricular Function in Patients With Cardiomyopathy and Left Bundle Branch Block

Abstract: LBBB is associated with a smaller degree of LVEF improvement compared with other QRS morphologies, even with GDMT. Some patients with LBBB may benefit from CRT earlier than guidelines currently recommend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 43 publications
3
61
0
Order By: Relevance
“…Some patients who exhibit left bundle branch block (LBBB) improve less on optimal medical therapy alone and often present mid-range EF. [ 47 ] This association of LBBB and HFmrEF raises the question as to whether this cohort of patients may benefit significantly from expanding the indications for implantation of a CRT device to LVEF >35%, particularly in the absence of reasons other than LBBB itself as the cause of LV dysfunction. [ 48 ]…”
Section: Predictors Of Lvef Transitionmentioning
confidence: 99%
“…Some patients who exhibit left bundle branch block (LBBB) improve less on optimal medical therapy alone and often present mid-range EF. [ 47 ] This association of LBBB and HFmrEF raises the question as to whether this cohort of patients may benefit significantly from expanding the indications for implantation of a CRT device to LVEF >35%, particularly in the absence of reasons other than LBBB itself as the cause of LV dysfunction. [ 48 ]…”
Section: Predictors Of Lvef Transitionmentioning
confidence: 99%
“…[9][10][11] More recent work now suggests that LBBB in itself may represent a previously unrecognized cause of LV dysfunction and may impair left ventricular recovery. 12 In the present analysis the authors set out to investigate the LBBB and its relationship with mechanical dyssynchrony using myocardial perfusion imaging (MPI) and vector electrocardiography (VECG, another surrogate of mechanical myocyte activation, derived form an ECG analysis). In a retrospective analysis the authors selected 45 patients with LBBB and 24 controls out of a cohort of 994 patients.…”
Section: See Related Article Pp 1227-1239mentioning
confidence: 99%
“…Prior studies have shown an increased risk of overt cardiovascular disease and mortality with LBBB, with a relative risk ratio of 3.78 between isolated LBBB and development of LVSD 4,5 . In addition, multiple studies have illustrated the impaired response of patients with LBBB and both ischemic and nonischemic cardiomyopathies to guideline‐directed medical therapy (GDMT) 6,7 . Furthermore, the presence of LBBB is associated with worse mortality in patients with preexisting LVSD 8 .…”
Section: Introductionmentioning
confidence: 99%